PAVOL STRAUSS – A GENIUS OUTSIDER - Žilka, Tibor (Porównania, 2019)
The aim of this paper regarding Pavol Strauss‘ Literary Work in the Central European Context is to introduce Pavol Strauss as a man and a writer, who was with his heart and soul a Central European. He had a strong bound to this territory spatially and temporally. At first, he was chased as a Jew, later on in the age of 30 he converted into Catholic. During the period of Stalinism, they considered him a second-class citizen, and he was wrongly called the clero-fascists however he was a believing Catholic. He was literally active in the second half of the 1930s, when he published two poetic collections in German. His poems in German were influenced by avant-garde which he became in touch with in Prague – its literary atmosphere defined Pavol Strauss’ literary experiments and further orientation. When speaking of Prague, also think of Franz Kafka, Franz Werfel and, of course, Reiner Maria Rilke. From the literary point of view, Pavol Strauss with his literary essays reached the highest level along with famous authors (R. Musil, K. Kraus, H. Broch). For his 82 years long life, Pavol Strauss cured many patients and left rare books of a unique philosophical dimension.